Pengembangan Membran Magnesol untuk Pemurnian Biodiesel - Saiful, Saiful; Nurfitriana, Nurfitriana; Ramli, Muliadi; Maulana, Ilham (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2013)
Magnesol membrane has been prepared by mixing chitosan polymer with magnesol particles via phase inversion method. The optimum compositions of adsorptive membranes were 3% chitosan, 15% DMF and 60% loading adsorbent. The porosity of these membranes was 34,17% and swelling degree was 51,91%. The membrane clean water flux was 224,4 Lm2h1 at a transmembrane pressure of 2.5 bar. The adsorptive membrane possesses an open and interconnected porous structure with a large surface area available for biodiesel purities adsorption. The results showed that after contacting in 60 minutes, numbers of acid value was reduced as 81,12% which is in accordance with value of SNI quality standards. In addition, the soap content adsorbed was 86,74% as potassium soap and 86,73% as sodium soap. The regenerated membrane can be reused with mantaining the high adsorption capacity. The methanol was better than ethanol to regenerate the magnesol membrane. The Magnesol membrane will be a new alternative method for biodiesel purification.Keywords: biodiesel, membrane adsorption, chitosan, magnesol, acid number, soap